COMMUNICATION VOICE ASIAN OF TEACHERS - Gunadi, YS (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2009)
The Brother hood of Asian Trade Unions (BATU) invites metoparticipate in the Congressof the Asian Con federation of Teachers (ACT) that will be conducted from 25-30 December 2007 at the YMCAI nternational Hotel, Chiang Mai, Thailand.By the congress, explaned about teachers honorat Provencialof Banten for the examples. In the same time, by aclamation,YS.Gunadi from FESDIKARIof lndoensia has bechosenas Vice President Asian Confederation of Teachers, 2007-2012 piriode